Annual report on education spending in England: 2022 - Elaine Drayton; Christine Farquharson; Kate Ogden; Luke Sibieta; Imran Tahir; Ben Waltmann (Institute for Fiscal Studies (IFS), 2022)
This is our fifth annual report on education spending funded by the Nuffield Foundation. It seeks to provide a clear and consistent comparison of the level and changes in spending per student across different stages of education. Following on from cuts to most areas of education spending during the 2010s, the government has provided additional funding at successive spending reviews between 2019 and 2021. However, rising levels of inflation and cost pressures have dampened the effects of extra funding, putting severe strain on providers' budgets right across the public sector. High ambitions for the education sector will also be harder to achieve in an era of further constraints on public spending.
Keywords: 330; Education and skills; Government finances and spending; Education spending; Education; Further education; Higher education; Government spending; Schools